Proces "wymywania" otoczenia przez Wrocław - ośrodek metropolitalny regionu dolnośląskiego - Obrębalski, Marek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The paper presents a problem of increasing of spatial socio-economic differences between metropolitan center and its surroundings. Negative symptoms of practical functioning of potency and gravitation mechanism are clearly observed in Lower Silesia region. It refers among others to permanent decreasing of share of jeleniogorsko-walbrzyski and legnicki subregions in total regional Gross Domestic Product and also to decreasing GDP per capita in these subregions. It is a very unfavorable process in relation to Wrocław and wrocławski subregion. Many towns (for example Jelenia Gora) were degraded as an effect of backwashing process of subregions surrounded Wrocław metropolitan area. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1143, s. 149-153